Mapping the Challenges in Distance Learning for Students with Disabilities during Covid-19 Pandemic: Survey of Special Education Teachers - Mahardika Supratiwi; Munawir Yusuf; Fadjri Kirana Anggarani (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2021)
The rapid spread of the Covid-19 virus has had an impact on various aspects of life, such as the economy, education, and socialisation. One of the social distancing policies in the field of education is the application of distance learning at the preschool, primary school, secondary school, special school, and college education levels. Its implementation has led to challenges for teachers, students, and parents, especially students with disabilities (SWD). The purpose of this study is to identify the challenges faced by the special education teachers (SETs) who have been providing distance learning for children with special needs during the Covid-19 pandemic. The study was conducted using a survey method by distributing questionnaires via Google Forms to 226 SETs in Indonesia. Data analysis was conducted using descriptive statistics. The results show that most of the SETs (66%) stated that they had faced barriers to distance learning that came from parents, students, and other teachers, as well as technical barriers. According to the SETs’ perceptions, some of the barriers that came from parents included lack of coordination and communication, limited use of mobile phones, and limited time for parents to accompany the students. The barriers coming from students were boredom and their lack of abilities. Furthermore, the barriers from the SETs themselves included difficulties in adapting material to online learning, difficulties in monitoring and evaluating student progress, and the lack of direction and coordination from schools. Other technical barriers were the frequent blackouts and insufficient internet signal.